“Are You People Jewish?” The Mistaken Identity of Mary Rosenblatt in the 1952 Harry Lee Murder Case - Halpern, Monda (Canadian Jewish Studies / Études juives canadiennes, 2015)
In June 1952, wife and mother Mary Rosenblatt was shot and killed in Sheffield, Ontario – allegedly by her lover Harry Lee. Lee, a mixed-race man, was hanged for the crime nine months later. In the six decades following his death, Rosenblatt has been consistently described as Jewish, yet Rosenblatt was, in fact, not Jewish. What factors contributed to this ethnic/religious misrecognition, and what can be gained by “remembering” Mary in this way? The case and the flawed collective memory suggest complex perceptions of Judaism, evident in the racialized way that Rosenblatt’s imagined Jewishness can be used to mitigate both Lee’s racial and sexual transgressions. En juin 1952, l’épouse et mère Mary Rosenblatt est assassinée à Sheffield en Ontario – prétendument par son amant Harry Lee. Lee, un homme « métis », est pendu neuf mois plus tard. Jusqu’à aujourd’hui, Rosenblatt a régulièrement été décrite comme juive. Pourtant, elle ne l’est pas. Qu’est-ce qui a contribué à cette erreur ethnique/religieuse et comment comprendre que l’on se « souvienne » de Mary de cette manière? Ce cas et la mémoire collective erronée qui en a découlé font ressortir des perceptions complexes du judaïsme, qui sont mises en évidence dans la manière dont la judéité inventée de Rosenblatt a pu être utilisée pour nuancer la transgression raciale et sexuelle de Lee.